The The Sense of Loss in Memorial Spaces: 'Absence' vs. 'Presence' - Zhou, Yuhan; Ren, Yuwei (Landscape Architecture and Art, 2024)
In recent years, memorial parks have garnered increased attention as spaces for public commemoration and individual reflection. However, despite their growing significance, many contemporary memorials have been criticised for over-reliance on abstraction and a lack of tangible connections to memory, limiting their ability to engage visitors’ perspectives effectively. This research explores the interplay of presence and absence in the design of memorial parks, focusing on their role in engaging visitors’ sensory perceptions and fostering emotional connections to memory. Through an analysis of the Vietnam Veterans Memorial and the 9/11 Memorial, this research identifies and categorises four standard design methods that utilise presence and absence to evoke reflection and remembrance. In this context, presence refers to visual or audible elements, such as reflections and repetition. At the same time, absence encompasses inaudible and invisible features like negative space and cut-outs. These methods operate not as isolated elements but within a dynamic continuum where presence and absence blend and transition, creating spaces that resonate with individual and collective memories of loss. By examining the application of these design methods in both case studies, this paper elucidates how memorial landscapes can evoke a profound sense of loss, providing visitors with a space to confront and reflect upon historical trauma. This analysis contributes to a deeper understanding of the fluid boundaries between presence and absence in commemorative design, offering insights into how these concepts can be employed to enhance the emotional and sensory engagement of memorial spaces.